Propuesta de mejora a los procesos de la Coordinación Académica de las carreras de la ESPAM MFL - Delgado Zamora, Karen Valentina (2017)
The objective of this research was to propose improvements to the Academic Coordination processes of ESPAM MFL careers, in order to find measures to improve the performance of each of the involved representatives, so that the different activities that are performed in them, for which scientific research techniques such as interviewing, observation, value added analysis were used, which, together with the application of process files, allowed methodological development of research, once applied techniques it was identified that the sub processes of studies homologation and validation to student admission and the sub-process of registration of assistance to teachers are not efficient and this creates inconveniences in the academic coordinators what prevents to obtain a more efficient process, that is why it is proceeded to give improvements to these sub processes through a proposal and thus can be developed with the activities in such a way that contributes to the institution and each dependency that exists in it.